The Characterization of pigments by spectrophotometry in a strain of Dunaliella viridis, isolated from the Ecuasal salt ponds (Revista Científica Ciencias Naturales y Ambientales, 2016)
In this work we evaluated the growth and pigment production of a strain of the halotolerant microalgae Dunaliella viridis (UGB-SE-3001), isolated from ECUASAL salt ponds, in the province of Santa Elena, Ecuador. For this purpose, discontinuous cultures on Johnson medium at different concentrations of NaCl (0.1 M, 0.5 M, 1 M, 2 M, 3 M and 4.5 M) were achieved. The culture conditions were pH 7.5, 24±2ºC, photoperiod 12:12, constant aeration and bilateral irradiance at 284 μmol/m2s. The treatments that yielded a higher cell production were 0.5 M with 2.72 ± 0.15E+07 cells/mL, followed by 1 M treatment with 2.21 ± 0.2E +07 cells/mL. The treatment with a higher pigment production was 1 M with 9.98 ± 1.08 μg/mL chlorophyll a, 3.44 ± 1.54 μg/mL chlorophyll b and 4.10 ± 0.57 μg/mL carotene. The optimum salt concentration range for growth of Dunaliella viridis is between 0.5 M and 1 M; it is displayed a negative correlation between salinity, cellular density and pigment production from 0.5 M salt concentration.
Keywords: Dunaliella viridis; spectrophotometer; pigments